Apparent vascular hypertension associated with Amoebic Gill Disease affected Atlantic salmon (Salmo salar) in Tasmania - Powell, MD; Forster, ME; Barbara Nowak (2002)
The dorsal aortic (DAP), ventral aortic (VAP) blood pressures and heart rate were measured in Atlantic salmon affected with AGD in a clinical outbreak. DAP and VAP were high compared with published values for other salmonid species. Fish subjected to a 3-h freshwater bath and returned to seawater (the treatment of choice for AGD control) had a significantly lower dorsal aortic pressure, with values comparable to those for other salmonids. Heart rate was not affected by freshwater exposure. These data suggest that there may be a vascular hypertension associated with AGD in Atlantic salmon. Although the source of the hypertension remains to be identified, this finding may help to explain the poor post-stress survival of AGD-affected salmon.